PENGARUH PENGGUNAAN METODE KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR IPS SISWA PADA MATERI POKOK MASUK DAN BERKEMBANGNYA AGAMA ISLAM DI INDONESIA KELAS XI SMA NEGERI 7 PADANGSIDIMPUAN - Ansyor Hasibuan (Pendidikan Sejarah, 2019)
The aims of this research to know a significant influence the use of cooperative methods STAD against IPS learning outcomes of students in entry on the subject matter and the development of the religion of Islam in Indonesia class XI SMA Negeri 7 Padangsidimpuan . The population is all of the research is 161 student and the sample was taken through cluster random sampling technique from population, so the sample is 26 student. The data obtained were analyzed in two stages. The first stage by using a statistical test correlation “r” product moment and to know whether there is an effect or not is use ttes formula. The result of analyzed obtained by an average of 3,21 on X variable with the category “good” and Y variable obtained 72,69 category “good”. The result of analyzed data score of tcount is smaller then ttable (rxy = 0,703 < 2,064), based on the result of the research, it can be concluded that the alternative hypothesis in this research cannot be accepted the truth.